Leveraging online social networks for people with disabilities in emergency communications and recovery. (8th March 2010) - Bricout, John C.; Baker, Paul M.A.
Information and Communication Technologies (ICTs) can play an important role in leveraging social networks for emergency communications and recovery involving persons with disabilities, provided that proper consideration is given to the strengths and weaknesses of the distributed nature of online resources in relation to the instrumental, psychological and social needs of persons with disabilities in the context of disasters or other emergency events. Emergency and disaster events inherently involve uncertainty and dynamic risk factors, and pose design and implementation challenges for inclusive planning and delivery systems. The involvement of persons with disabilities as key stakeholders throughout the developmental and evaluation process is critical to the effectiveness of online social networks in bridging real-world concerns with virtual resources. An analytical model for understanding the role of distributed networks in mediating the negative impacts of a disaster or an emergency on persons with disabilities is proposed, together with key objectives for change.